PENGELOLAAN SARANA DAN PRASARANA DI SEKOLAH DASAR NEGERI 01 TOHUDAN, KARANGANYAR - Bandono, Wahyu Ardhi; Samino, Samino (Profesi Pendidikan Dasar, 2015)
The purpose of this study are (1) to describe the characteristics of the provision offacilities and infrastructures; (2) to describe the characteristics distribution of facilitiesand infrastructures; (3) too describe the characteristics of facilities and infrastructuresmaintenance. This research uses qualitative research and ethnographic research design. Datawas collected through observation, interview, and documentation. Model analysis of thedata in this study uses cross-site analytical methods for description. The results of thestudy are (1) Provision of facilities and infrastructure in 01 Tohudan Elementary School heldby planning needs of infrastructure were prepared at the start of the new academic year, alongwith the preparation of the budget revenue and expenditure plan prepared in discussion ofschool community which consists of principals, teachers, school committee, and the schooljanitor. (2) The direct distribution applied the goods done at once, the items that have beenreceived and in inventoried directly distributed to the principal, teacher, or school guard.While the indirect distribution is not completed at onces, so before the distribution completes,it cannot be handed over to the concerned, in addition to the indirect distribution occur if thereare remaining infrastructure. (3) Maintenance of infrastructure study conducted by teacherswith students by keeping the facilities and infrastructure and put in the available space.And if there is damage, the infrastructure which cannot be handled by the teacher, the teacherreports verbally to the school principal and followed up with a written report to the principal.